A Study of Echocardiographic Changes in Patients with Newly Diagnosed Primary Hypothyroidism: A Cross-sectional Study - Khatri, Prabin; Sapkota , Suman; Neupane, Aryan; Gautam, Narayan; Subedi, Saphal Nath; Banjade, Ashish; Kharel, Smile (Europasian Journal of Medical Sciences, 2025)
Background: Hypothyroidism is known to cause reversible cardiac dysfunction in humans. Thyroid hormone alters the cardiovascular hemodynamics. This study was performed to assess echocardiographic changes in untreated newly diagnosed primary hypothyroid states as such studies are scarce in our setting. Methods: This hospital based cross-sectional study was conducted among 71 patients with newly diagnosed primary hypothyroidism who presented to the medicine outpatient department, at Universal College of Medical Sciences and Teaching Hospital (UCMS-TH), Bhairahawa, Nepal from December 2018 to June 2020 after taking ethical clearance from institutional review committee (UCMS/IRC/212/18). Thyroid function test and echocardiography were carried out in patients under study. The data was analyzed with SPSS Version 16. Results: A total of 71 patients (52 females and 19 males) with primary hypothyroidism were enrolled for the study. Among these 58 cases were overt/clinical hypothyroidism, and 13 cases were subclinical hypothyroidism. Echocardiography was abnormal in 63.4% of cases with 43.7% showing diastolic dysfunction, 18.3% diastolic interventricular septal thickness abnormality, 8.5% diastolic left ventricular posterior wall thickness abnormality, and 8.4% pericardial effusion. Conclusion: Our study found diastolic dysfunction, diastolic interventricular septal thickness abnormality, diastolic left ventricular posterior wall thickness abnormality, and pericardial effusion as the common echocardiographic change in patients with newly diagnosed primary hypothyroidism. Therefore, our study highlights the need for cardiac evaluation of patients with primary hypothyroidism so that early intervention can be performed to improve the clinical outcome.